Public Debatable Position of Woman as Witnesses in Marriage: The Perspective of Islamic and Constitutional Laws - Burlian, Paisol P (Italian Sociological Review, 2018)
Position of women as witnesses in Islamic marriage procession is still debated till now. In Indonesian Muslim community, there are two contradictive ideas appeared; first, women have not been allowed to be witnesses not only in marriage process, but also in the divorce, and hudud; second, women could be the witnesses, as long as the number of double and accompanied by a man. This research compares the position of women as a marriage witnesses in the perspective of Islamic and Constitutional Laws. A normative legal method was applied in this Comparative Research. Data found showed that there was no gap for women to be witnesses in a marriage. As stated in the 25th article of the Compilation of Islamic Law (CIL) of Indonesia which designates as the witnesses in the marriage ceremony are males. They are Muslim who are fair, adults (Aqeel/ baligh), uninterrupted memory and not deaf or hard of hearing. Therefore, this research recommends to renew the CIL, because in 25th article of CIL provides an opportunity for women to be marriage witnesses. It is expected to President and law makers in Indonesia should consider for Judicial Review of CIL.